PP10 Effect of exercise intensity on energy intake and energy expenditure in obese and lean individuals. (21st October 2014) - Shamlan, Ghalia; Robertson, MD; Collins, Adam
Abstract : Appetite control (i.e. control of energy intake) is important for weight maintenance. Moreover, exercise contributes to the most variable component of energy expenditure but its impact is beyond the energy cost of exercise including physiological, behavioural, and appetite effects (Spiegelman and Flier JS. Cell . 2001; 104 :531–43). Exercise is known to acutely influence effect appetite but evidence as to the independent effect of intensity is lacking (Martins et al., J Clin Endocrinol Metab . 2010; 95 :1609–16). This study investigated the role of exercise intensity on appetite, energy intake (EI), energy expenditure and subjective measures of appetite. One hour after a standardised breakfast, 30 healthy normal- weight volunteers 30 lean and 10 obese. Subjects undertook either 8 repeated 60 second bouts of cycling at 95% VO2 max (high intensity) or 30 min of continuous cycling, at a fixed cadence, equivalent to 50% of the participant's VO2 max (low intensity) in a randomised crossover design. Satiety was assessed subjectively throughout the study using visual analogue scales. Ad libitum intake of a pasta meal was measured at the end (3-h post-breakfast). No significant effect of exercise was observed on the ad libitum meal or 24 h energy intake post-exercise. For lean group, HI significantly increased energy expenditure compared to LI post-exercise (p = .001) with a significant difference in fat oxidation level. No significant differences were observed in energy intake of fat for 2 days post-exercise between two intensities for both groups. In conclusion, there are mechanisms and consequences of exercise in short and long-term appetite control; however, these mechanisms warrant further explanation. These results support the need for future research in to the role of in regulation energy balance, especially for obese people.